Percepção da equipe da estratégia saúde da familia sobre a atuação da equipe de saúde bucal em Goiânia-GO - SOARES, érika Fernandes (2010)
The aim of this study was to investigate the perception of professionals from the Brazilian Family Health Strategy (BFHS) on the performance of the dental health team in Goiânia-GO, Brazil. We have conducted a qualitative study using focus group technique to collect data. Four focus groups were held with health professionals of the BFHS who had worked with oral health teams for at least one year. Sample included community health workers (N= 11), assistant nurses (N= 5), nurses (N= 4) and doctors (N= 4) from ten BFHS health centers. During data collection professional categories were grouped according to level of formal education. The topics covered were the ideal characteristics for a dentist working in the BFHS, activities undertaken by the oral health team and opinion about the performance of this team. The interviews were transcribed and data were analyzed using a thematic analysis of content. For the professionals interviewed, the characteristics that a dentist should have in order to work in the BFHS are: profile to work in the public health field, communication skills, good interpersonal relationship, ethics, creativity in difficult situations and emotional balance. The respondents perception on the performance of the oral health team is affected by the great volume of treatment needs which result in high demand and short supply, as well as by frequent problems with equipment and resources supply. Although the interpersonal relationship of the oral health team with the other professionals and the community was considered positive, opinion regarding the impact of the actions on the oral health condition of the population covered by the BFHS is divided.